2000
DOI: 10.7589/0090-3558-36.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury Accumulation in Tissues and Its Effects on Growth and Appetite in Captive Great Egrets

Abstract: To test the hypothesis that fledging wading birds would be more at risk from mercury toxicosis than younger nestlings, captive great egret nestlings were maintained as controls or were dosed from 1- to 14-wk-old with 0.5 or 5 mg methylmercury chloride/kg wet weight in fish. Birds dosed with 5 mg/kg suffered from subacute toxicosis at wk 10-12. Growing feather concentrations were the most closely correlated with cumulative mercury consumed per weight. Blood concentrations of mercury increased more rapidly after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 49 publications
9
103
3
Order By: Relevance
“…Fournier et al, (2002) found loon chicks, experimentally dosed with MeHg concentrations substantially greater than those found in nature, were still able to effectively depurate much of the MeHg into emerging feathers. When juvenile feather molt ends, blood MeHg levels thereafter increase (Spalding et al, 2000a;Fournier et al, 2002). This ability to rapidly transfer blood MeHg into growing feathers partly accounts for the significant difference in blood Hg levels between adults and juveniles prior to fledging.…”
Section: Age Affects Hg Exposurementioning
confidence: 97%
“…Fournier et al, (2002) found loon chicks, experimentally dosed with MeHg concentrations substantially greater than those found in nature, were still able to effectively depurate much of the MeHg into emerging feathers. When juvenile feather molt ends, blood MeHg levels thereafter increase (Spalding et al, 2000a;Fournier et al, 2002). This ability to rapidly transfer blood MeHg into growing feathers partly accounts for the significant difference in blood Hg levels between adults and juveniles prior to fledging.…”
Section: Age Affects Hg Exposurementioning
confidence: 97%
“…Mercury levels in the livers of some specimens approached or exceeded those recorded in experimental poisonings of similarly piscivorus gray herons (Ardea cinerea) (Van Der Molen, 1982) and juvenile great egrets (Ardea albus) (Spalding et al, 2000). On the other hand, it has recently been shown that the mercury in the livers of common loons is principally in the less toxic inorganic form, and that the methylmercury fraction of the total declines as total mercury increases, generally remaining below 2.8 mg/kg (Pokras et al, 1998;Scheuhammer et al, 1998).…”
mentioning
confidence: 99%
“…Effects have been demonstrated in both laboratory Gochfeld 2000, 2005;Spalding et al 2000a;Hoffman et al 2011) and field studies Frederick et al 1999;Jackson et al 2011). While most pollutants are anthropogenic in nature, oil and mercury also can come from natural sources.…”
Section: Pollutantsmentioning
confidence: 99%